2016
DOI: 10.1542/peds.2016-0124
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Immune Thrombocytopenia After Influenza Vaccination: A Case Report

Abstract: Immune thrombocytopenia (ITP) is an isolated autoimmune condition, often preceded by a viral infection. Vaccines, mainly the measles-mumps-rubella vaccine, have also been associated with an increased risk of developing the disease. Although some case reports of ITP after influenza immunization in adults have been published, epidemiologic studies examining the role of the influenza vaccine as a trigger of ITP have not conclusively proven causality. We report a child with 3 occurrences of ITP, each within 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…The possibility of recurrent ITP associated with vaccines other than MMR is even less wel-described. There is one case report in literature describing recurrent ITP associated with repeated influenza vaccination 18. In our case, the patient had an initial episode of MMR vaccine-associated ITP followed by an episode of ITP after being immunised with vaccines other than MMR, although it is impossible to determine which of the Tdap-IPV, pneumococcal and meningococcal vaccines was the trigger.…”
Section: Discussionmentioning
confidence: 80%
“…The possibility of recurrent ITP associated with vaccines other than MMR is even less wel-described. There is one case report in literature describing recurrent ITP associated with repeated influenza vaccination 18. In our case, the patient had an initial episode of MMR vaccine-associated ITP followed by an episode of ITP after being immunised with vaccines other than MMR, although it is impossible to determine which of the Tdap-IPV, pneumococcal and meningococcal vaccines was the trigger.…”
Section: Discussionmentioning
confidence: 80%
“…Prior retrospective studies showed that there is a risk of developing ITP after receiving measles-mumps-rubella, hepatitis A, varicella and diphtheria-tetanus-pertussis vaccines in children and adolescents 3. A number of case-control studies and case reports regarding post-influenza vaccination ITP have been published 4–8. Vaccine-associated ITP may be caused by molecular mimicry, which demands the activation of autoreactive B or T cells by peptides in the vaccine that display structural parallel to antigens found on platelets 3.…”
Section: Discussionmentioning
confidence: 99%
“…The time frame of development of ITP in relation to the epistaxis is notable in this case. At least one case report has had a child develop three occurrences of ITP, each within 1 week of receiving the influenza trivalent vaccine 7. It is possible that with first exposure, there is a prolonged period of time before symptoms and that repeat exposures produce an anamnestic, symptomatic response which is both more brisk and more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Immune thrombocytopenia purpura (ITP) was reported and reviewed as an AEFI following administration of measlesmumps-rubella, hepatitis B, and hepatitis A vaccinations [6,7]. A study by Hamiel et al recounted bleeding symptoms as a manifestation of thrombocytopenia in a patient receiving the influenza vaccine [8]. Susanah et al reported bleeding manifestations as AEFI cases in West Java Province, Indonesia, most due to vitamin K deficiency, followed by cases caused by underlying diseases, either hereditary hemostasis disorders such as hemophilia, or acquired hemostasis disorders such as dengue hemorrhagic fever [9].…”
Section: Introductionmentioning
confidence: 99%